2003
DOI: 10.1210/jc.2002-021511
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pulse Wave Velocity Associated with Reduced Calcaneal Quantitative Osteo-sono Index: Possible Relationship Between Atherosclerosis and Osteopenia

Abstract: Although the associations between arterial calcification or advanced atherosclerosis and osteopenia have been well documented, it is not clear whether the one is the result of the other or they coprogress from the early stages through common mechanisms. Thus, we measured pulse wave velocity (PWV), which reflects earlier phase atherosclerosis, and osteo-sono assessment index (OSI), which correlates with bone mineral density, in 7865 Japanese subjects (4183 males and 3682 females, aged 50 +/- 12 yr) and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 51 publications
5
44
1
3
Order By: Relevance
“…BMD at the femoral neck was significantly and inversely correlated with common carotid artery intima-media thickness (IMT) and pulse wave velocity (PWV) in postmenopausal women with osteoporosis 3) . Moreover, a similar tendency in healthy subjects independent of common risk factors for osteoporosis and CVD was found 4,5) . A longitudinal study showed that a decrease in BMD was significantly associated with increased aortic calcification scores 6) .…”
Section: Introductionsupporting
confidence: 62%
“…BMD at the femoral neck was significantly and inversely correlated with common carotid artery intima-media thickness (IMT) and pulse wave velocity (PWV) in postmenopausal women with osteoporosis 3) . Moreover, a similar tendency in healthy subjects independent of common risk factors for osteoporosis and CVD was found 4,5) . A longitudinal study showed that a decrease in BMD was significantly associated with increased aortic calcification scores 6) .…”
Section: Introductionsupporting
confidence: 62%
“…Increased brachial-ankle PWV values have also been reported in subjects with osteoporosis or sarcopenia [40][41][42] .…”
Section: Other Risk Factors For Cardiovascular Diseasementioning
confidence: 91%
“…By contrast, previous studies have shown a negative correlation between A negative correlation was reported between PWV and bone mineral density (BMD) (17).…”
Section: Discussionmentioning
confidence: 78%